Three-way actuation of shape memory composite (Archives of Mechanics - Test, 2011)
The SMC belt composed of two kinds of SMAs with different phase transformation temperatures and SMP, was fabricated and the three-way (reciprocating) movement and recovery force in bending actuation were investigated. The results obtained can be summarized as follows. 1) The three-way bending movement was achived during heating and cooling, based on the characteristics of the SMA tapes and the SMP tape. 2) The recovery force decreased at first and increased thereafter during heating and decreased during cooling. The recovery force was roughly estimated by the proposed model. 3) The development and application of multi-functional SMCs with simple structure for three-dimensional actuators are highly expected.